Management Control System and Organizational Performance of Manufacturing Firms in Kailali District - Mahara, Mahendra Singh (KMC Journal, 2025)
This study examines the relationship between management control systems and the organizational performance of manufacturing firms in Kailali District. Management control system (MCS) is a crucial tool for strategic planning, budgeting, decision-making and internal auditing for the enhancement of organizational performance. The study looks into the effects of these tools on organizational performance. The study evaluates the significance of MCS components using descriptive statistics, correlation analysis and multiple regression using primary data from 20 manufacturing organizations. The results show that internal audits, strategic planning and decision-making have positively and significantly affected organizational performance. However, budget control has a positive relationship but insignificant effect on organizational performance. Among all the management control system dimensions strategic planning has been found most important dimension to affect the organizational performance of manufacturing firms. The findings of the study will be useful to the managers of manufacturing firms for the implementation of management control dimensions. The study added an area of comparison regarding the management control system.